Transformation Of Education Management Through The Integration Of Artificial Intelligence In The Development Of Decision Support Systems For The Strengthening Of Inclusive Education - Pebi Julianto (Rey Media Grafika, 2026)
The transformation of education management through the integration of artificial intelligence (AI) is increasingly seen as a key strategy in strengthening decision support systems for inclusive education. This study aims to analyze the application of AI technology in education management, evaluate decision support system mechanisms that support inclusive governance, identify implementation challenges, and formulate an integrative framework for effective AI adoption. The results show that predictive analytics, natural language processing, and resource optimization algorithms are the most dominant AI applications in education management. These technologies enable more proactive data-driven decision-making, increase resource allocation efficiency by 25–40%, and reinforce the principle of fairness in inclusive education. However, AI implementation faces challenges related to data integration, infrastructure readiness, organizational resistance, and the need for managerial competency development. These findings emphasize that the success of AI integration depends not only on technological sophistication, but also on strategic alignment, leadership support, and continuous evaluation mechanisms. Overall, this research contributes theoretically and practically to the development of adaptive, accountable AI-based education management that is oriented toward improving the quality of inclusive education.